Pintando o sete : matemática e artes nos anos iniciais do ensino fundamental - Santos, Josenilson Felizardo dos (2015)
The Mathematics´ Teaching and Learning process is still, no doubt, a complex and problematic issue in the Brazilian Education context. Discipline with a lowest accomplishment and a higher failure level, as the results of educational evaluations have shown, it has been a source for discussions as well as academic and educational policy studies. Talking about Art, another focus in this study, there is a kind of devaluation of it as a part of the knowledge constitution, being this duality one of the possible barriers to the interdisciplinary use of these knowledge fields in teaching. Similarly, motivated by the possibilities of the use of art as an aid to the Mathematics´ teaching and learning process during the initial grades of Elementary School, we define as an objective of this study to investigate the knowledge and the teacher´s practices concerning the relation of Art and Mathematics during the initial grades of Elementary School. The mentioned research was developed in a Local School at Aracaju (a city in Sergipe - Brazil), designated to the five first grades of Elementary School. The main subjects of this research are two teachers of the second and fourth grades of Elementary School. For the understanding of the study´s target, we appealed to theorists who develop connected researches, directly or indirectly, to the investigation pivot such as Nacarato, Lorenzato, Brizuela, Ferreira, Barbosa, Pereira, Read Fazenda, Silva, Tardif, Japiassú, Freire, D´Ambrosio, Fusari, Fiorentini, Pimenta, among others. The research, with a qualitative approach, it has been characterized as an ethnographic study in the perspective told by André (1995) it had a fieldwork fulfilled between June and July in 2014, with questionnaire appliance, interviews and the observation with a solid description as the procedures. The research aroused a greater reflection about the relevance of the relation between Art and Mathematics in the classroom. It was possible to realize the effort of the teachers in making the Mathematics class stimulator, making use of specific tools offered by Art. We found out that the imposition of the methodological accomplishment from some educational institutions have made it difficult to apply an interdisciplinary methodology. We also found out that the greater difficulty of the relation between Arts and Mathematics in teaching it might has been caused by the lack of a specific education training, as well as a continued education to teachers of the initial grades of Elementary School. Consequently, we realize a constant fight from these teachers to overcome the lack of time to find ways of planning in a stimulator manner to their educational practice, equally to adapt themselves to the several disciplinary possibilities in this practice.